2016
DOI: 10.1590/s1518-8787.2016050006209
|View full text |Cite
|
Sign up to set email alerts
|

Trends in corrected lung cancer mortality rates in Brazil and regions

Abstract: OBJECTIVE To describe the trend in cancer mortality rates in Brazil and regions before and after correction for underreporting of deaths and redistribution of ill-defined and nonspecific causes.METHODS The study used data of deaths from lung cancer among the population aged from 30 to 69 years, notified to the Mortality Information System between 1996 and 2011, corrected for underreporting of deaths, non-registered sex and age , and causes with ill-defined or garbage codes according to sex, age, and region. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
18
0
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 20 publications
4
18
0
9
Order By: Relevance
“…Corroborating the findings of this study, analysis of the trend of mortality from lung cancer from 1996 to 2011 in Brazil in people aged 30-69 years also observed higher mortality rates in men, with a reduction of mortality for men in the country and in all regions, and an increase for women, except for the north region 22 . Another study on the trend of lung cancer mortality from 1980 to 2007, analyzing the effects of "age," "period," and "cohort", also found higher mortality rates in men.…”
Section: Discussionsupporting
confidence: 84%
“…Corroborating the findings of this study, analysis of the trend of mortality from lung cancer from 1996 to 2011 in Brazil in people aged 30-69 years also observed higher mortality rates in men, with a reduction of mortality for men in the country and in all regions, and an increase for women, except for the north region 22 . Another study on the trend of lung cancer mortality from 1980 to 2007, analyzing the effects of "age," "period," and "cohort", also found higher mortality rates in men.…”
Section: Discussionsupporting
confidence: 84%
“…The lung cancer mortality rates were significantly higher among men compared to women, but with decreasing trends among men and increasing trends among women, in Brazil. This finding is in agreement with previous www.nature.com/scientificreports/ studies conducted in the country 10,[22][23][24] .International studies assessing worldwide lung cancer trends across five continents have also found similar results 25,26 . The increase in disease mortality among women is partly attributable to an increase in tobacco use in recent decades 22 .…”
Section: Discussionsupporting
confidence: 93%
“…Despite a reduction in lung cancer mortality among men in Brazil, there was an increase among the Federative Units with low HDIs, such as those in the Northeast and Rondonia, while in the Federative Units with the highest HDIs, there was a declining trend in mortality rates. Similar results were found by Guerra et al 9 in a study conducted between 1990 and 2015; however, these findings are in contrast to those from a study by Malta et al 10 , conducted between 1996 and 2011, which found a decreasing trend in lung cancer mortality in the Northeast and North.…”
Section: Discussionsupporting
confidence: 76%
“…During 1996-2011, a study was done on the age group of 30-69 years old to assess the trends in lung cancer mortality. In the aforementioned study, a reduction trend was identified among men and but an increase trend among women; however, higher rates of lung cancer-induced mortality was detected among men (Malta et al, 2016).…”
Section: Discussionmentioning
confidence: 81%